The mediating role of meaningful work in the relationship between servant leadership and knowledge hiding behaviors - Hatiboglu, Muhammed Bugrahan; Ceyhan, Semih; Ekmekcioglu, Emre Burak (EMERALD GROUP PUBLISHING LTD, 2026)
Purpose - This research aims to investigate the relationship between servant leadership and employee's knowledge hiding behaviors, as mediated by meaningful work. Based on the social learning theory (SLT), the research suggests that servant leaders are exemplary role models, which enhance the employee perception of meaning of work, subsequently counteracting disengaging behaviors like knowledge hiding. Design/methodology/approach - Data were collected from 609 employees in T & uuml;rkiye via a student-recruited sampling. The study used structural equation modelling to test direct and indirect relationships among servant leadership, meaningful work and knowledge hiding. Findings - Servant leadership was found to directly decrease playing dumb, and to not significantly affect evasive or rationalized knowledge hiding. Nonetheless, meaningful work provides insight into how servant leadership serves to decrease knowledge hiding through reduced playing dumb and evasive hiding. This shows that servant leadership reduces knowledge hiding primarily through fostering employees' perceptions of meaningful work. Practical implications - The findings underscore the importance of leadership development and job design that helps employees feel their work is meaningful. Incorporating servant leadership into these practices, organizations can design specific interventions to curb knowledge hiding encourage teamwork or cultivate a trust climate at workplace. Originality/value - This study advances the literature by identifying meaningful work as a key mechanism through which servant leadership affects knowledge hiding. Based on SLT, it describes how servant leaders influence employees' knowledge hiding behaviors through the modelling processes. Expanding beyond the one-dimensional representation of knowledge hiding and focusing on its different behavioral dimensions, the study provides a nuanced account of how servant leadership can deter knowledge hiding behaviors.
Keywords: : Servant leadership; Knowledge hiding; Meaningful work; PERFORMANCE; WORKPLACE; MODEL; HIDE; Information Science & Library Science; Business & Economics